Pengetahuan dan sikap dengan pelaksanaan perilaku hidup bersih dan sehat (PHBS) - Haqqoni, Habib Fatih; Rahmadewi, Triani; Arifah, Siti (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Clean and Healthy Living Behavior (PHBS) is an important effort to improve health and prevent various diseases, but its implementation in Indonesia is still not optimal. Low PHBS implementation has resulted in high incidences of diseases such as diarrhea and dengue fever. Purpose: This study aims to determine the relationship between knowledge and attitudes with the implementation of clean and healthy living behavior (PHBS). Method: This study used a descriptive correlational design with a cross-sectional approach conducted at Muhammadiyah 1 Wates Junior High School. The research respondents were 71 students using the entire population or so-called total sampling technique. The research instrument used a questionnaire on knowledge and attitudes regarding the implementation of PHBS. Data analysis was carried out using the Spearman rank correlation test. Results: The Spearman rank obtained a correlation coefficient value between the level of knowledge and PHBS with a p-value of 0.311 > 0.05 and a correlation value between the level of attitude and PHBS with a p-value = 0.720 > 0.05 which indicates that there is no significant relationship between knowledge and attitudes with the implementation of PHBS in students, with a negative relationship direction and less correlation strength. Conclusion: The results of the relationship analysis using the Spearman correlation test show that there is no significant relationship between the level of knowledge and the implementation of PHBS, and there is no significant relationship between the level of attitude and the implementation of PHBS (p > 0.05). Keywords: Attitude; Clean And Healthy Living Behavior; Knowledge. Pendahuluan: PHBS merupakan upaya penting dalam meningkatkan derajat kesehatan dan mencegah berbagai penyakit, namun penerapannya di Indonesia masih belum optimal. Rendahnya pelaksanaan PHBS berdampak pada tingginya kejadian penyakit seperti diare dan demam berdarah. Tujuan: Untuk mengetahui hubungan antara pengetahuan dan sikap dengan pelaksanaan PHBS. Metode: Penelitian ini menggunakan desain deskriptif korelasional dengan pendekatan cross sectional yang dilakukan di SMP Muhammadiyah 1 Wates. Responden penelitian adalah siswa sebanyak 71 orang dengan menggunakan keseluruhan populasi atau disebut teknik total sampling. Instrumen penelitian menggunakan kuesioner pengetahuan dan sikap dengan pelaksanaan PHBS. Analisis data dilakukan menggunakan uji korelasi spearman rank. Hasil: Uji spearman rank diperoleh nilai koefisiensi korelasi antara tingkat pengetahuan dengan PHBS dengan p-value 0.311 >0.05 dan nilai korelasi antara tingkat sikap dengan PHBS dengan p-value = 0.720 > 0.05 yang menunjukan tidak adanya hubungan yang signifikan antara pengetahuan dan sikap dengan pelaksanaan PHBS pada siswa, dengan arah hubungan negative dan kekuatan korelasi kurang. Simpulan: Hasil analisis hubungan menggunakan uji korelasi Spearman menunjukkan bahwa tidak terdapat hubungan yang bermakna antara tingkat pengetahuan dengan pelaksanaan PHBS, serta tidak terdapat hubungan yang bermakna antara tingkat sikap dengan pelaksanaan PHBS (p > 0.05). Keywords: Pengetahuan; Perilaku Hidup Bersih dan Sehat (PHBS); Sikap.